A STUDY OF RESEARCH NOTIONS IN WIRELESS BODY SENSOR NETWORK (WBSN) - Kumar, Dinesh; Kalaipriyan, T.; Raghav, R.S. (IRO Journal on Sustainable Wireless Systems, 2019)
The Body Sensor Networks is captivated in gathering the communication module in a more reliable manner along with efficiency in terms of energy, more secure than earlier schema's, ands enhanced utilization of resources. Wireless BAN (WBAN) has the tendency to be placed even inside the human body. The significance of BSN has the tendency to go through all aspects such as fitness of a person, his/her health issues, caring in critical level, and so on. In 2014 [1] the elevation of body sensors has been grown upto 420 millions from 11 million units in 2009. In this research work, we addressed BAN from On-Body to Body-to-Body cooperative networks at different levels: propagation, protocols and localization applications.
Keywords: Wireless Sensors; Body Sensors; Security and Research Trends